Features of the Accumulation of Heavy Metals in the "Soil-Clover" System And Their Influence on the Microbial Price of Soil in the Conditions of the Urban Environment - E. V. Bondar; E. I. Kharina; N. I. Gandraburova; A. V. Antonova; A. A. Stavitskaya (Наука. Инновации. Технологии, 2022)
Introduction. The article touches upon the issues of ecological safety of the environment. The analysis of the content of heavy metals in the soil-clover system in an urban environment has been carried out. The results of the analysis made it possible to identify the levels of accumulation of heavy metals in the underground part of the red clover (Trifolium pratense L.) (growing in an urban environment with a high degree of technogenic load), as well as to establish their influence on the microbial cenosis of the soil. Materials and methods of the research. Methods of sampling carried out in accordance with the Methodical instructions for the determination of heavy metals in the soils of farmland and crop production. The study included evaluation of absorption intensities biological indicator elements and biogeochemical activity. Statistical analysis of the results was carried out with the use of application software package «Statistica for Windows», version 6.0, and the software «Microsoft Excel 2016». Microbiological analysis was carried out in accordance with regulatory documents. Counting of grown colonies was carried out using a Scan 300 Interscience colony counter. Methods of mathematical statistics were used to analyze the results. The results of the study and their discussion. According to the data obtained, the most common pollutants in the urban environment are metals such as Ni, Cd, Pb, Cu, Mn. However, the data values of these heavy metals in the root portion of clover does not exceed the value of MACs and MPCs in the soil. Microbiological analysis showed that increased concentrations of nickel and iron inhibit the growth of Rhizobium trifolii, and different concentrations of cadmium and manganese stimulate the growth of bacterial culture. Conclusions. The resulting values for heavy metals in the root of the clover did not exceed the background content in the soils of the city, which means that the root system blocks the low of heavy metals in the plant. The different nature of the influence of heavy metals on nitrogen-fixing microorganisms has been established. Increased concentrations of heavy metals such as cadmium and manganese stimulate the growth of Rhizobium trifolii. Under the action of nickel and iron on this microorganism, a depressing effect is noted. High concentrations of these metals dramatically inhibit the growth of nitrogen-ixing bacteria, which may further affect soil fertility.